2015
DOI: 10.1016/j.sbspro.2015.06.111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Playing Chess on the Concentration of ADHD Students in the 2nd Cycle

Abstract: The study examines the effect of playing chess on the concentration of students with Attention Deficit Hyperactivity Disorder (N=14, age: 11-13). The study hypothesized that chess improves concentration period and listening language skills. The sample was chosen from two schools with inclusion, students received chess training twice per week. Pre-and post-measurements of Conner's Teachers Rating Scale: Revised-Long version, concentration tasks, and scores of school language listening tests were the data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Examples of board games include chess, Go, and Shogi. Research involving chess, which is played by two players on a board with 64 black and white squares and 16 pieces for each player [1], has contributed to the theoretical development of cognitive psychology [2]. For example, Burgoyne et al [3] conducted a meta-analysis and demonstrated that chess skills are significantly and positively correlated with four broad cognitive abilities: fluid reasoning, comprehension-knowledge, short-term memory, and processing speed.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of board games include chess, Go, and Shogi. Research involving chess, which is played by two players on a board with 64 black and white squares and 16 pieces for each player [1], has contributed to the theoretical development of cognitive psychology [2]. For example, Burgoyne et al [3] conducted a meta-analysis and demonstrated that chess skills are significantly and positively correlated with four broad cognitive abilities: fluid reasoning, comprehension-knowledge, short-term memory, and processing speed.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in the literature are also similar to this result. (Aksoy and Gönültaş, 2020;Nour ElDaou and El-Shamieh, 2015;). It was concluded that most of the chess coaches, pre-school teachers and pre-school field experts addressed that the program is applicable in all conditions (physical, educational, social, financial, etc.).…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The game of chess was also described in several studies as a tool used in intervention programs for improving the outcomes and the quality of life for specific categories of people, especially vulnerable ones. Some studies report the results from chess training programs implemented in educational settings ( Jerrim et al, 2016 ; Jankovic and Novak, 2019 ), or the effectiveness of playing chess as a treatment option for children with ADHD ( ElDaou and El-Shamieh, 2015 ; Blasco-Fontecilla et al, 2016 ). This type of intervention programs was also used with the aim of improving general cognitive status, attention, processing speed, and executive functions in a sample of semi-institutionalized and institutionalized senior people ( Cibeira et al, 2021 ), for the elderly with dementia ( Wahyu Laksono et al, 2019 ), or to evaluate the benefits of chess in mathematics lessons for children with learning disabilities ( Scholz et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%